Abacavir + dolutegravir + lamivudine for the treatment of HIV. (12th October 2016) - Comi, Laura; Maggiolo, Franco
ABSTRACT: Introduction : Since the last revision of both European and American guidelines (EACS and DHHS), new data from clinical trials and cohort studies, as well as experience in clinical practice, have prompted significant changes to the list of recommended/preferred options for the treatment of HIV infected patients, highlighted the role of INSTI-based regimens. Dolutegravir (DTG) in combination with abacavir/lamivudine (ABC/3TC) is one of these preferred regimens in multiple clinical scenarios, including treatment-naive and treatment-experienced patients. Areas covered : In this article we describe the coformulation of ABC/3TC/DTG in a fixed-dose combination (FDC) approved in September 2014 for the treatment of HIV infection. We focused our research on the efficacy and safety data resulting from phase 2 and 3 clinical study, particularly on the results of both SPRING (1 and 2) and SINGLE studies. Expert opinion : Triple combination therapy with ABC/3TC/DTG should be considered among the initial options for treatment-naive patients, being effective, well tolerated, with a high genetic barrier to resistance along with a convenient once-daily administration. In treatment-experienced patients the single-tablet regimen (STR) based on ABC/3TC/DTG could be used as simplification strategy in subjects with sustained viral suppression, as the high genetic barrier of DTG should ensure a safe switch from both NNRTI or PI based regimens.